Сутність та зміст поняття «екологічна культура» - Біда Олена; Bida Olena; Орос Ільдіко; Orosz Ildikó; Oros Ildiko; Кучай Тетяна; Kucsáj Tetjána; Kuchai Tatiana (РВВ ЦДПУ ім. В. Винниченка, 2021)
Резюме. У статті доведено, що культура складається з чотирьох основних елементів: поняття (концепти), відносини, цінності, правила та норми. Кожна з цих складових має надзвичайно важливу роль у створенні культурного іміджу та екологічної освіти фахівців. Виокремлено найважливішу функцію культури – вона є способом, за допомогою якого суспільство вирішує проблеми.

Abstract. Taking into account modern world trends, the formation of ecological culture in young people acquires special significance in Ukraine. As is well known, culture is a complex of subjectivations and objectifications that must be assimilated in the process of cross-cultural education and used in everyday orientation. The basics of formation of ecological culture in youth are revealed. Culture is a complex of subjectivations and objectifications that must be assimilated in the process of cross-cultural education and used in everyday orientation. It was found that the purpose of ecological culture is to form a system of scientific knowledge, views, beliefs, which lay the foundations for a responsible attitude to the environment. The article proves that culture consists of four main elements: concepts, attitudes, values, rules and norms. Each of these components has an extremely important role in creating the cultural image and environmental education of professionals; to meet modern requirements for a specialist requires a new approach to the problems of educating a new formation, healthy, mobile, competitive, morally mature, professional and cultural, ready for active life in modern socio-cultural realities, which are still in the learning process. The most important function of culture is highlighted - it is the way in which society solves problems. In essence, ecological culture is a kind of «code of human behavior» with nature itself and with the «second nature» – a new branch of human activity, which is created in the process of work and aimed at human self-realization on scientifically sound positions and conclusions. Culture consists of four main elements: concepts, attitudes, values, rules and norms. Each of these components has an extremely important role in creating the cultural image and environmental education of professionals. The most important function of culture is that it is the way in which society solves problems. Taking into account modern world tendencies, formation of ecological culture in youth acquires special value in Ukraine.
Essence and content of the concept of «ecological culture»
Keywords: культура; екологічна культура; основні елементи культури; culture; ecological culture; basic elements of culture; preservation and strengthening of health